Effect of soluble salts in electrolytic manganese residue on its geotechnical characteristics. (15th August 2023) - Lu, Ting; Wei, Zuoan; Li, Shilong; Wang, Ya; Wang, Wensong; Yang, Yonghao; Zheng, Binbin
Abstract: Electrolytic Manganese Residue (EMR) is a solid waste containing soluble sulfate, discharged by electrolytic manganese industries. The accumulation of EMR in ponds poses a significant hazard to both safety and the environment. This study utilized innovative geotechnical test techniques to conduct a series of tests, investigating the effect of soluble salts on the geotechnical characteristics of EMR. The results revealed that soluble sulfates had a significant impact on the geotechnical characteristics of the EMR. In particular, the infiltration of water leached away the soluble salts, causing a non-uniform particle size distribution and decreasing the shear strength, stiffness, and liquefaction resistance of the EMR. Nevertheless, an increase in the stacking density of EMR could improve its mechanical characteristics and inhibited the dissolution of soluble salts. Therefore, increasing the density of stacked EMR, ensuring the effectiveness and non-obstruction of the water interception facilities, and reducing rainwater infiltration could be effective measures to enhance the safety and reduce the environmental hazard of EMR ponds. Highlights: Characteristics of EMR were investigated to assess its hazard. Experimental methods were optimized to account for the presence of soluble salts. Soluble salts proved to be advantageous for the mechanical properties of EMR. Dissolution of soluble salts is detrimental and requires attention for EMR ponds.